INFLUENCY OF CUTTING TOOL’S ANGLE ON MILLING OF COMPOSITE MATERIALS PERFORMED BY ROBOTS - Barbosa, Gustavo Franco; Savazzi, José Otávio (Brazilian Journal of Operations & Production Management, 2016)
Nowadays, the aircraft manufacturing environment has searched for new features related to machining operations in order to improve the performance faced to production requirements. The machining process in aerospace industry has been and will continue to grow at a very high rate due to the high variety of materials to be processed. On this way, composite materials have been largely used as a construction material for parts, components, wings, fuselage sections and furniture of business jets. Especially for the furniture fabrication, one key challenge of the manufacturers is the ability to efficiently machine the composite materials by different parameters, thickness, and also the entry and exit of the tool on the piece. In this context, this work presents an evaluation of the robot behavior when the cutting tool’s angles are changed during the milling of composite materials associated to the forces involved during the milling that can reduce the lifetime of the robot. It contributes to improvement of the quality and cycles times beyond to get more reliability and productivity for the business, besides how to do a better entry and exit in the composite avoiding damages on robots and wear of tools. All benefits of this new research are shown on a case study of an industrial example.